Determination Of Nitrite Content In Pharmaceutical Products By High Performance Liquid Chromatography With Fluorescence Detection (Cuestiones de Fisioterapia, 2025)
Nitrite is present everywhere including water, solvents, and the environment. When it combines with amides and secondary amines, leads to generation of N-nitrosamines, that behave as a carcinogenic agent. During the production drug or products may have these impurities such as N-nitrosamines due to the employment of reagents, catalysts, solvents, or raw ingredients, which has amides or secondary amines groups during. Therefore, determination of nitrite content is very important at initial stage to find out the possible of Nnitrosamines. Different approaches have been used to determine the nitrite content in the various samples.